Effects of magnesium addition on microhardness in eutectic Al-Si-Mg Alloys - Abdul Razak Daud,; Ibrahim Abu Talib,; Mohd Harun, (Universiti Kebangsaan Malaysia, 2001)
The eutectic Al-Si-Mg alloys were prepared and heat treated at 327oC and 540oC for 10 hours and followed by ageing at 160oC for various ageing times. The microhardness of the alloys increased as the ageing time and magnesium content increased. The addition of magnesium as well as ageing strengthened the matrix and improved the second phase morphology.